STUDI AGRIBISNIS DAN FAKTOR YANG MEMPENGARUHI PRODUKSI KELAPA HIBRIDA (STUDI KASUS PADA AGRIBISNIS KELAPA (Cocos nucifera L) NARYO DI DESA SALEH JAYA KECAMATAN AIR SALEH KABUPATEN BANYUASIN) - Widodo, Adman; Iskandar, Sutarmo; Iswarini, Harniatun (Societa: Jurnal Ilmu-Ilmu Agribisnis, 2016)
Studi Of Agribusiness and Production Factors That Affencing Production of Coconut Hyibrida (Cocos nucifera L). Case Study in NaryoÃ¢â¬â¢s Coconut Agribusiness in Saleh Jaya Vilage Air Saleh District Banyuasi Regency. The purpose of this study was to determine the application of agribusiness coconuts in Saleh Jaya District of Air Saleh banyuasin. To determine the factors that influence the production of coconuts in Saleh Jaya District of Air Saleh banyuasin.Then to investigate the income of coconut farmers ( Naryo ) in Saleh Jaya District of Air Saleh banyuasin. This research was conducted in the village of Saleh Jaya District or Air Saleh Banyuasin from March until May 2016. The method used was a case study , to methods of sampling was done on purpose. Data collection methods used in this study is the observation and direct interview to the respondents who have been determined by using tools such as quisoner that has been prepared in advance. Tabulation data processing is done then analyzed by descriptive qualitative approach and descriptive analysis with mathematical approach. The results showed that, Agribusiness Studies and Production Factors Affecting Production of Coconut include: Acquisition Subsystem Production Facilities, Subsystems Farming, Marketing Subsystem. Factors Affecting Includes: Labor , KCL fertilizer, Urea, Fertilizers SP36, Gramoxone. Factors that significantly influence the production of coconut production are: urea, fertilizer KCL, SP36, Gramoxone and factors that influence non significant to coconut production are: labor. Sales activities performed by the coconut palm growers is to be purchased directly by the collector.